Governance of securities clearing and settlement systems - Daniela Russo; Terry L. Hart; Chryssa Papathanassiou (European Central Bank (ECB), 2004)
In the context of securities clearing and settlement systems, the nature of governance arrangements acquires a dimension that goes beyond their traditional function in corporate law. They constitute a tool for regulators and central banks to achieve their respective policy goals relating to market operation, market integrity, and systemic stability. In the light of the analysis of this paper, and pending a further evolution in the regulation of securities clearing and settlement in the Community, the following conclusions can be drawn. Whatever the model of corporate governance used in a jurisdiction, securities clearing and settlement systems should adopt and ensure effective implementation of the highest corporate governance standards or best practices adopted or recommended for companies in the jurisdiction in which it operates as such standards or practices evolve over time. Generally, this would imply that securities clearing and settlement systems at minimum should adopt and implement the best practices recommended for listed companies. Additionally, a securities clearing or settlement system should adopt corporate governance mechanisms adequate to address the interests of users and the public in the operation of the system. Such mechanisms should be organized so that the criteria followed to select participants on the board or on specialized committees are established ex ante. Board members should also take into account the interests of users and the public in board decisions, in particular, those relating to qualifications for system access, fair pricing, the integrity of the risk management system, innovation and efficiency, and the achievement of the policy objectives of competent authorities. Securities clearing and settlement systems should make adequate disclosures regarding their corporate governance arrangements so that users and the public can ascertain the manner in which conflicts of interest among owners, the board, users and the public interest are prevented, resolved or mitigated. Corporate governance arrangements of securities clearing and settlement systems should be the subject of adequate regulation and oversight to ensure that services are provided at fair prices to users under fair and equitable conditions of access; that the risk management programs of system operators are effective; that risk management decisions are not affected by considerations extraneous to the risk management function; and that, to the maximum extent possible, functional service providers compete in equivalent conditions of competition. Looking forward, the adoption of a harmonized regulatory regime for securities clearing and settlement systems should be considered to complete the internal market within the Community and to better achieve the policy goals identified in this paper relating to the governance of those systems.
Keywords: G29; G34; L49; K2; 330; clearing; settlement; governance; risk management; oversight.; Clearing; Wertpapierhandel; EU-Staaten